This Is Not Reality (Ceci n'est pas la réalité): Capturing the Imagination of the People Creativity, the Chinese Subaltern, and Documentary Storytelling - Paola Voci (Global Storytelling)
How has documentary(re)presented subaltern creativity? Focusing on post-socialist, globalizing China, I examine documentary narratives by and about the creative subaltern originating from Chinese “cool cities” and expanding in the virtual space of global digital media. In these narratives, the creative subaltern has appeared obliquely, tangential to other narratives, subordinate to internationally recognized artists, or with a more central role, as the author or the protagonist of documentary films. I analyze these narratives’ entanglement with elitist definitions of creativity, the representation of subaltern reality, the expression of subjectivity, and the tension between the political and the personal. I argue that documentary has played an important albeit ambiguous role—provocative and empowering, but also, at times, formulaic and constricting—in shaping the discourse on the subaltern as a creative subject, by amplifying creativity’s indexicality to the real and obfuscating its imaginative quality and its ambition of breaking free from the real. Reflecting on the contemporary relevance of the Free Cinema movement’s advocacy for a subjective, personal approach to capturing the “imagination of the people” and exploration of lyric realism in documentary filmmaking, I propose that documentary can and should dare to “make poetry.” Forms of documentary expressivity such as poetic, not plot-driven narratives can reconcile imagination with reality and offer alternative, more appropriate means of capturing the complexity, heterogeneity, and contradictoriness of the subaltern condition, and for subaltern creativity to be expressed, appreciated, and affirmed.